Patients and informal caregivers' experiences of burden of treatment in lung cancer and chronic obstructive pulmonary disease (COPD): a systematic review and synthesis of qualitative research. Issue 2 (5th February 2019) - Lippiett, Kate Alice; Richardson, Alison; Myall, Michelle; Cummings, Amanda; May, Carl R
Abstract : Objective: To identify, characterise and explain common and specific features of the experience of treatment burden in relation to patients living with lung cancer or chronic obstructive pulmonary disease (COPD) and their informal caregivers. Design: Systematic review and interpretative synthesis of primary qualitative studies. Papers were analysed using constant comparison and directed qualitative content analysis. Data sources: CINAHL, EMBASE, MEDLINE, PsychINFO, Scopus and Web of Science searched from January 2006 to December 2015. Eligibility criteria for selecting studies: Primary qualitative studies in English where participants were patients with lung cancer or COPD and/or their informal caregivers, aged >18 years that contain descriptions of experiences of interacting with health or social care in Europe, North America and Australia. Results: We identified 127 articles with 1769 patients and 491 informal caregivers. Patients, informal caregivers and healthcare professionals (HCPs) acknowledged lung cancer's existential threat. Managing treatment workload was a priority in this condition, characterised by a short illness trajectory. Treatment workload was generally well supported by an immediacy of access to healthcare systems and a clear treatment pathway. Conversely, patients, informal caregivers and HCPs typically did not recognise or understand COPD. Treatment workload was balanced with the demands of everyday life throughout a characteristically long illness trajectory. Consequently, treatment workload was complicated by difficulties of access to, and navigation of, healthcare systems, and a fragmented treatment pathway. In both conditions, patients' capacity to manage workload was enhanced by the support of family and friends, peers and HCPs and diminished by illness/smoking-related stigma and social isolation. Conclusion: This interpretative synthesis has affirmed significant differences in treatment workload between lung cancer and COPD. It has demonstrated the importance of the capacity patients have to manage their workload in both conditions. This suggests a workload which exceeds capacity may be a primary driver of treatment burden. PROSPERO registration number: CRD42016048191.